1973
DOI: 10.1136/bmj.3.5873.207
|View full text |Cite
|
Sign up to set email alerts
|

Androsteroneetiocholanolone Ratios in Male Homosexuals

Abstract: SummaryAnalyses of 24-hour specimens of urine from healthy adult males for androsterone and etiocholanolone produced values which, when calculated as discrinant scores, discriminated between heterosexual and exclusively homosexual individuals. This confirms a previous study.No significant differences were found between heterosexuals and homosexuals in parental ages, secondary sex characteristics, genitalia, anthropometry, 17-ketosteroids, and 17-ketogenic steroids.A significant difference was found between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Interestingly, in the 1970s there were some thoughts that the ratios of androsterone and etiocholanolone discriminated between heterosexual and exclusively homosexual individuals, clearly indicating that androsterone and etiocholanolone lead to a new sexual phenotype [47]. Looking at enzyme activities, especially 11-beta dehydrogenase (11-beta HSD), there was a striking difference in the ratio of (THF + 5aTHF)/THE between both Asperger syndrome (21.5) and Kanner’s syndrome (19.7) groups and their matched controls (2.8 and 1.3, respectively) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the 1970s there were some thoughts that the ratios of androsterone and etiocholanolone discriminated between heterosexual and exclusively homosexual individuals, clearly indicating that androsterone and etiocholanolone lead to a new sexual phenotype [47]. Looking at enzyme activities, especially 11-beta dehydrogenase (11-beta HSD), there was a striking difference in the ratio of (THF + 5aTHF)/THE between both Asperger syndrome (21.5) and Kanner’s syndrome (19.7) groups and their matched controls (2.8 and 1.3, respectively) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently accepted that steroid profile changes prenatal to postnatal and androgen biosynthesis during minipuberty favors the backdoor pathway over the classic pathway with several pathologic associations (21-Hydroxylase Deficiency, Fragile-X-Syndrome or an altered sexual development. [16,20,21,22,23,24,25] Despite limited by a relatively small sample size especially for girls a significant increase for boys but not girls of the two androgens Androsterone and Eticholanolone during puberty persists. The increased androgens during this sensitive period of development might additionally promote autistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The backdoor pathway provides a (more) efficient route to DHT. [20] It was indicated that backdoor pathways plays an important role in human hyperandrogenic disorders such as 21-Hydroxylase Deficiency, Fragile-X-Syndrome or an altered sexual development [20,21,22,23,24,25] but also in physiological states such as mini puberty. [20,26,27,28] O'Shaugnessy could show, that the main androgen of the backdoor pathway is Androsterone (A).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The varied and conflicting results have more or less cancelled each other out, and have revealed methodological naiveties reminiscent of early biochemical studies of schizophrenia. Two studies both reported an abnormal ratio of androsterone to etiocholanolone in the urine (both breakdown products of testosterone) but the relevance of such a finding remains obscure (Margolese & Janiger, 1973;Evans, 1972). The most sophisticated approach has been the search for the typically female positive feedback response of the hypothalamus to oestrogen provocation, as a possible indicator of incomplete masculinization of the male homosexual's brain.…”
mentioning
confidence: 99%